Răspuns :
9(2x-5)²-4(4x-3)²=
2(4x²+25-20x)-4(16x²+9-24x)=
8x²+50-40x-64x²-36+96x=
-56x²+14+56x=
=-14(4x²-1+x)
2(4x²+25-20x)-4(16x²+9-24x)=
8x²+50-40x-64x²-36+96x=
-56x²+14+56x=
=-14(4x²-1+x)
9( 2x - 5)² - 4( 4x - 3)² , se aplica formula a² - b² = ( a - b)( a + b)
= 3²( 2x - 5)² - 2²( 4x - 3)²
= [ 3( 2x - 5) - 2( 4x - 3)] [ 3( 2x - 5) + 2( 4x - 3)]
= ( 6x - 15 - 8x + 6)( 6x - 15 + 8x - 6)
= ( - 2x - 9)( 14x - 21)
= 3²( 2x - 5)² - 2²( 4x - 3)²
= [ 3( 2x - 5) - 2( 4x - 3)] [ 3( 2x - 5) + 2( 4x - 3)]
= ( 6x - 15 - 8x + 6)( 6x - 15 + 8x - 6)
= ( - 2x - 9)( 14x - 21)